PEMANFAATAN KAJIAN PEMETAAN BAHASA DALAM RANGKA PENYUSUNAN MATERI MUATAN LOKAL: STUDI KASUS BAHASA JAWA - Widada Hadisaputra (Balai Bahasa Sumatera Utara, 2019)
Language teaching in schools, both the Indonesian and regional languages, will always rests on the issue of the selection of materials as a matter of teaching languages, the languages that are considered standard. Standardization of language teaching materials would not only involve the standardization of the language itself, but also concerning standardization linguistic aspects of the language. For the determination of the standard language of the language, must be examined scientifically and to deliberate determination standard language that involves various stakeholders. In addition, certain variants determination as a representation that material must be preceded by a comprehensive study on the number of variants, the number of speakers, as well as the geographical distribution area (mapping language) from the use of these variants. Starting from the above reasoning, the study of the Java language mapping is helpful in determining the Java language teaching materials as local content material. It aims to solve the problem of language diversity, linguistic aspects, and other aspects that are given to students as teaching materials. The benefits derived from the study of the Java language is at least contained practical benefits for teaching the Java language, which reduce the gap in the Java language teaching in the province of Central Java. All regions have similar views, policies, and implementation of the Java language teaching, which in turn will achieve the level of success of language teaching balance among regions exist.